IMPLEMENTASI PROGRESSIVE WEB APPS PADA MARKETPLACE - Iskandar, Edi; Buwono, Robby Cokro; Putri, Sintia Ogi Nindiya (STMIK Palangkaraya, 2022)
Marketplace is a website or online application that facilitates the buying and selling process from various stores. One of the reasons why the marketplace is famous is because of the ease and convenience of use. Many describe online marketplaces as department stores. The next problem experienced by users, because every smartphone has limitations in installing applications, so the choice to install native applications is considered due to limited resources and can cause smartphone performance to be slow. Using Progressive Web Apps (PWA) can be a solution to overcome the problem where PWA can run like a native application installed on a smartphone. The implementation of the resulting system can help users in online transactions that save smartphone memory and market place applications have been tested on smartphones, resulting in screenshots of the application running as expected.